Determinants and Cost Efficiency of Leasing and Purchasing Decisions for Heavy Equipment in the Palm Oil Industry - Pancanto Kuat Prabowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The lease or purchase decision for heavy equipment directly affects operational efficiency in palm oil operations, including loading, material handling, and land maintenance. This study aims to analyze the factors influencing procurement decisions for wheel loaders, excavators, and skid-steer loaders, and to evaluate the cost efficiency of leasing versus purchasing at a state-owned palm oil mill in Riau Province. The research employed a mixed explanatory approach combining quantitative and qualitative data. Quantitative data consisted of 42 observations of hour-meter utilization and 36 months of operational cost records obtained from company documents. Qualitative data were collected through in-depth interviews with eight informants, including production managers, an operations manager, procurement department heads, a cost-planning analyst, and heavy equipment supervisors. Quantitative analysis applied the total cost of ownership and life cycle costing, while qualitative data were examined using thematic analysis. The findings indicate that wheel loaders and skid steer loaders are more cost-efficient to purchase due to their high utilization rates and lower long-term hourly costs. In contrast, excavators are more economical to lease due to intermittent use and higher maintenance risks. These findings indicate that procurement policies should consider utilization patterns, operational risks, and cost structures to enhance efficiency and operational stability.